Creating a Broader Impacts Culture - Shakila Merchant; Jackie L Weissman; Effie MacLachlan (The University of Alabama, 2024)
Minority-serving institutions (MSIs), historically Black colleges and universities, and Tribal colleges and universities play a pivotal role in championing inclusivity and diversity within higher education systems across the nation. As catalysts for social change, they regularly engage in Broader Impacts (BI) work. However, these institutions often face challenges in resource allocation and a dearth of human capital to sustain vital operations, which hinders their capacity building efforts. This article explores how MSIs, exemplified by the City College of the City University of New York (CUNY), can empower faculty, staff, and trainees engaged in BI work to extend their influence beyond their institutions by adopting a community of practice and engagement (COPE) approach. By leveraging collective strengths of knowledge, expertise, and diversity, CUNY's MSI campuses endeavor to foster a transformative ripple effect, shaping a more inclusive and equitable future through research and innovation. Beginning in Spring 2023, the City College of New York, in partnership with the Advancing Research Impact in Society (ARIS) National Science Foundation-funded center, embarked on initiatives to understand the existing BI culture, knowledge, and challenges to enhance BI and research development capacity across the CUNY system. This article discusses the pilot efforts and lessons learned from these endeavors.